The Role of Instagram in Developing Halal Fashion Business: A Literature Review - Anisatul Maghfiroh; Sirajul Arifin (Institut Agama Islam Al-Fatimah Bojonegoro, 2024)
This study examines the role of Instagram in the development of halal fashion businesses using a descriptive analysis approach. By systematically reviewing relevant literature, the research identifies effective marketing strategies used by halal fashion brands on Instagram and evaluates their impact on brand awareness, consumer engagement, and purchasing decisions. The analysis includes case studies of successful halal fashion brands that utilize Instagram as their primary marketing platform. The findings reveal that Instagram significantly enhances brand visibility and consumer engagement, particularly through credible influencer marketing and compelling visual storytelling. Interactive features: comments, likes, and stories have been shown to strengthen the relationship between brands and consumers, while collaborations with influencers aligned with Islamic values positively influence purchasing decisions. This study contributes to the existing literature by providing practical guidelines for halal fashion businesses to leverage Instagram while effectively maintaining adherence to Shariah principles. It underscores the potential of integrating modern marketing techniques with Islamic ethics to expand reach and strengthen brand equity in the halal fashion industry